Prevalence of anxiety and depression in ecuadorian adolescents - Marina del Rocío Ramírez Zhindón; Angel Ricardo Ramón Herrera; David Mauricio Ortega Jimenez (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Objective: To determine the prevalence and incidence of anxiety disorders and depression with loneliness in a sample of adolescents.  Material and methodology: Quantitative, correlational, cross-sectional study including 330 Ecuadorian adolescents selected by non-probabilistic purposive sampling. The Ad Hoc Questionnaire, the Depression, Anxiety, and Stress Scale (DASS-21), and the UCLA Loneliness Scale were used for data collection.  Results: Of the 330 adolescents, 65.5% were male, and the mean age was 16.8 years. Sixty, 60% are in their third year of high school and 39.4% are in their second year. Most of them live in the province of Pichincha 36.1%. In anxiety they present an average of 6.4 and in depression of 5.7; they have an average of 42 in loneliness. There is a positive correlation between anxiety, depression and loneliness. Finally, females have higher levels of depression.  Conclusion: Adolescents do not present anxiety or depression disorders, however, they present high levels of loneliness. There is a positive correlation between anxiety, depression, and loneliness, that is, the higher the levels of loneliness, the higher the probability that adolescents present anxiety or depression. Likewise, there is evidence of higher levels of depression in females.